2019
DOI: 10.1364/oe.27.014030
|View full text |Cite
|
Sign up to set email alerts
|

Long cavity ring fiber mode-locked laser with decreased net value of nonlinear polarization rotation

Abstract: We investigate a new configuration of a mode-locked fiber laser by using a nonlinear polarization rotation-based design to generate soliton pulses with low repetition rate. Unlike with previously reported configurations, we introduce a Faraday mirror after the first half of the cavity length to counteract the nonlinear polarization rotation effects. The total cavity length is 437 m including a 400-m long twisted SMF-28 fiber. The fiber was twisted to cancel the linear birefringence and to ensure that the polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…In the following the minimal transmission angle is referred to as 0° and the angle of maximal transmission is 100°. In our previously reported works used all-polarization control cavities [25][26][27]33] we experimentally found that the regimes of mode-locking operation depend on the polarization state in CW mode, before mode-locking is started. We will refer to this state as the initial polarization state.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…In the following the minimal transmission angle is referred to as 0° and the angle of maximal transmission is 100°. In our previously reported works used all-polarization control cavities [25][26][27]33] we experimentally found that the regimes of mode-locking operation depend on the polarization state in CW mode, before mode-locking is started. We will refer to this state as the initial polarization state.…”
Section: Resultsmentioning
confidence: 87%
“…Recently we proposed a new way to solve the problem of overdriving for long ring cavity lasers using NPR for mode-locking [27]. The handedness of NPR depends on the handedness of the polarization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High‐resolution in long fibre monitoring is of great interest in this context and a shorter duty cycle is very important [1, 2 ]. A comparison between duty cycle results in previous works [4, 6–9 ] is presented in Table 1. The present work shows the lowest duty cycle while maintaining a low repetition rate and ps‐long pulses.…”
Section: Resultsmentioning
confidence: 99%
“…A similar experiment has been reported in [4 ], but with a pulse, durations limited to the nanosecond scale, mainly due to dispersion effects within the ultra‐long cavity. While a number of works in the literature demonstrate either short pulse duration [6, 7 ] or low repetition rates [4, 8, 9 ], the present work employed dispersion management over the long‐length ring cavity allowing for stable fundamental mode‐locked pulses to be obtained with picoseconds temporal width and kHz repetition rate.…”
Section: Introductionmentioning
confidence: 99%